Routine Reversal of the AMOC in an Ocean Model Ensemble. Issue 24 (20th December 2022) - Dewar, William K.; Parfitt, Rhys; Wienders, Nicolas
Abstract: We describe a form of Atlantic Meridional Overturning Circulation (AMOC) variability that we believe has not previously appeared in observations or models. It is found in an ensemble of eddy‐resolving North Atlantic simulations that the AMOC frequently reverses in sign at ∼35°N with gyre‐wide anomalies in size and that reach throughout the water column. The duration of each reversal is roughly 1 month. The reversals are part of the annual AMOC cycle occurring in boreal winter, although not all years feature an actual reversal in sign. The occurrence of the reversals appears in our ensemble mean, suggesting it is a forced feature of the circulation. A partial explanation is found in an Ekman response to wind stress anomalies. Model ensemble simulations run with different combinations of climatological and realistic forcings argue that it is the atmospheric forcing specifically that results in the reversals, despite the signals extending into the deep ocean. Plain Language Summary: The Atlantic Meridional Overturning Circulation (AMOC) is a climatically important component of the ocean circulation. It is routinely thought to flow northward at the surface and southward at depths of 2, 000–3, 000 m. Here we show that a significant component of the annual AMOC cycles are intervals during which it actually reverses this sense of flow and argue further that this is a response of the AMOC to the atmosphere. The AMOC anomaly is basin scale in size and extends over the full depth. These results have implications for annual heat storage in the North Atlantic. Key Points: The Atlantic Meridional Overturning Circulation can reverse in sign Reversals appear in the annual cycle The reversals are the result of atmospheric forcing